Perceptions of factors influencing organisational attractiveness and professional development: A case study of graduate millennials in South Africa - Tladi, Tumelo (My University, 2017)
Designing graduate programmes which effectively attract, develop and retain talented graduates, remains a challenge for many host organisations. With the advent of the millennial generation joining the workforce, effective graduate programmes provide graduates with a safe action learning environment, enabling their smooth transition from the classroom to the workplace. This case study research investigated the most important work-related factors influencing organisational attractiveness as perceived by graduate millennials in South Africa. It also evaluated the effectiveness of a firm’s graduate programme in leading towards professional development. A mixed methodology approach utilising an online survey was undertaken on the firm’s graduate programme participants. The case study data was analysed using a combination of descriptive and statistical techniques. The key findings indicate that ‘opportunities for career progression’, ‘excellent training and development programmes’ and ‘competitive wages and other financial incentives’ are the most important work-related factors influencing organisational attractiveness. Furthermore, the firm’s graduate programme reported high levels of several job-related factors, including ‘co-worker support’, ‘learning opportunities’, ‘organisation satisfaction’, ‘task significance’ and ‘feedback’. These job-related factors have been found in previous research to strongly predict internship satisfaction and to have a positive effect on the professional development of graduates. These findings can assist host organisations to design effective graduate programmes, which lead towards the professional development of millennials in South Africa.
MBA Thesis
Keywords: Employee motivation,Job satisfaction,College graduates -- Employment South Africa